Fuzzy PWI-Ideals of Lattice Pseudo-Wajsberg Algebras - A. Ibrahim; M. Indhumathi (International Journal of Mathematics And its Applications, 2018)
In this paper, we introduce the notions of fuzzy pseudo-Wajsberg implicative ideal (fuzzy PWI-ideal) and fuzzy pseudo lattice ideal in lattice pseudo-Wajsberg algebra. Also, we obtain some of their related properties. Moreover, we investigate the properties of fuzzy PWI-ideal related to homomorphism and kernel.